Potential of Binahong and Ginger Functional Drink as An Alternative Food for Type 2 Diabetes Mellitus Patients - Firdaus Syafii; Ahmad Yani (Journal of Noncommunicable Diseases Prevention and Control, 2024)
Binahong and ginger are herbal plants with various bioactivities, including antidiabetic and antioxidant. One of the herbal drinks used in therapy for patients of type 2 diabetes mellitus (DMT2) is decoction from binahong leaves. This research used binahong leaves and ginger to make a functional drink rich in antioxidants for DMT2 patients. This research aimed to determine the effect of adding ginger on antioxidant activity and sensory tests and the antioxidant potential of binahong leaves decoction as a functional drink for DMT2 patients. The research design used was a completely randomized design with five formulations, namely F0 (0 grams of ginger), F1 (2 grams of ginger), F2 (5 grams of ginger), F3 (7 grams of ginger), and F4 (10 grams of ginger). The parameters tested were antioxidant activity and organoleptic attributes such as colour, taste, and aroma. The resulting data was then subjected to an ANOVA test at the 5% significance level. The results showed that F3 gave a different value (p<0.05) and gave the highest score to the organoleptic properties of taste (5.02) and aroma (5.03). The F4 formulation gave a different value (p<0.05) and gave the highest score for organoleptic properties of colour (5.45). Apart from that, F3 and F4 showed potent antioxidant activity, with IC50 values of 45.18 and 38.83 ppm. Thus, F3 and F4 have the potential to be developed as functional antioxidant drinks for DMT2 patients.